Change in mineral composition and cooking quality in legumes grown on semi-arid alfisols due to elevated CO2 and temperature - Shankar, K. Sreedevi; Vanaja, M.; Shankar, Mekala; Siddiqua, Asma; Sharma, K. L.; Girijaveni, V.; Singh, V. K. (Frontiers in Nutrition, 2025)
This study was conducted to determine the effects of elevated carbon dioxide (eCO 2 ) and temperature (eT) on phytochemical and nutritional parameters in legumes. Field experiments with black gram (Vigna mungo L.), green gram (Vigna radiate L.) and pigeonpea (Cajanus cajan L.) genotypes were carried under the Free Air Temperature Elevation (FATE) facility with three treatments (Ac , eT and eCO 2 + eT) at ICAR-CRIDA, Hyderabad. The results revealed that the degree of negative impact on both phytochemical and nutritional quality in the three crops was high under eT as compared eCO 2 + eT. The protein content decreased by 25.6% under eT + eCO 2 while ash content increased to the extent of 38.19% under eT+eCO 2 . The carbohydrate also decreased by 5.53% under eT+eCO 2. Under elevated conditions, extent of decline in micronutrient (Zn, Fe, Mn, and Cu) was higher as compared to P, Ca and Mg in the three crops. Also, the Principal component Analysis (PCA) model revealed that the major contributors to PC1 are Mg, crude fiber, cooking time, phosphorus, hydration capacity, Ash content and Mn.The major contributors to PC2 is swelling capacity, Cu, Mn, Carbohydrate, Hydration capacity, Zn while the major contributors to PC3 is Ca, Fe, Zn, Protein, Carbohydrate, swelling Index and Ash content with the eigen values of principal components calibrated through different parameters ranged from 1.052 to 4.755 in black gram, while they ranged from 1.073 to 6.267 in green gram. This study provides insights on nutritional quality under changing global climate scenario.